Charcot Neuroarthropathy: Current Surgical Management and Update. A Systematic Review - Bajuri, Mohd Yazid; Ong, Shir Lee; Das, Srijit; Mohamed, Isa Naina (Frontiers in Surgery, 2022)
Abstract Background Charcot neuroarthropathy of the ankle and hindfoot is a complex clinical entity with a high risk of amputation. Charcot neuroarthropathy limb reconstruction has been proposed as a limb salvaging procedure. However, there was a lack of information on the various available reconstruction methods, including the outcomes and complications. The present study aimed to evaluate the current literature and update on the trends regarding the surgical management of Charcot neuroarthropathy of the ankle and hindfoot. Methods All data published from January 2010 to January 2020 that investigated the methods of fixation and their respective outcomes for the surgical reconstruction in Charcot neuroarthropathy were analysed. The union rate, amputation rates, and complications associated with these techniques were taken for statistical analysis. Results A total of sixteen studies fit the inclusion criteria of this study, with four level III studies and twelve level IV study were included. Ten studies utilised internal fixation only; five used a combination of internal fixation and circular external fixator, whereby there are three comparative studies between internal and external fixation and two studies applied combined technique of internal and external fixation (hybrid fixation). One study describes the usage of circular external fixation only. Conclusions The use of retrograde intramedullary nail as a treatment of choice in reconstruction Charcot neuroarthropathy ankle before ulcer occurrence. Hydroxyapatite (HA)- coated screws are recommended for the locking mechanism to prevent migration in Charcot neuroarthropathy due to poor bony quality. Hybrid fixation is recommended for reconstruction in a condition of ulceration and more complex deformity as it provides a higher rate of limb salvage with less soft tissue irritation. Keywords Charcot; Neuroarthropathy; Neuropathy; ankle; hindfoot; Surgical reconstruction.